A halogen-free flame-retardant environmentally friendly cable
The poor mechanical properties of halogen-free cables are solved by using polyolefin and ethylene-vinyl acetate copolymer as the sheath layer substrate and adding flame retardant fillers with modified concave and concave rock stone and magnesium hydroxide. The problem of high performance and environmentally friendly halogen-free flame retardant cables are achieved.
Patent Information
- Application Number
- CN202411487207.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing halogen-free flame-retardant cables have shortcomings in terms of mechanical properties, and it is difficult to achieve the performance level of traditional halogen-containing flame-retardant cables.
Polyolefin and ethylene-vinyl acetate copolymer are used as the base material for the sheath layer, and a flame retardant filler composed of flame retardant and concave rock stone is added to improve the cable by modifying the combination of concave rock stone and magnesium hydroxide. flame retardant and mechanical properties.
It significantly improves the mechanical properties and flame retardant properties of halogen-free flame retardant cables, solves the problem of poor mechanical properties of traditional halogen-free cables, and meets environmental protection requirements.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to a halogen-free flame-retardant and environment-friendly cable. Background Art
[0002] In modern society, cables are widely used in power systems, communication networks, industrial automation, building facilities and other fields as important carriers of power and signal transmission. Whether it is the power supply network of the city, high-speed communication equipment, or complex automated production lines in factories, cables are like the nervous system, connecting various parts to ensure the stable transmission of power and information. Many flame-retardant cables in traditional cables use halogen flame retardants. From an environmental protection perspective, when halogen-containing cables are burned or disposed of, the halogenated substances released are difficult to degrade naturally and may penetrate into the soil and water bodies, causing long-term negative impacts on the ecosystem. Moreover, in the production process of cables, the synthesis of some halogen-containing materials may involve environmentally unfriendly chemical processes, resulting in hazardous waste and greenhouse gas emissions. With the continuous improvement of people's awareness of fire safety and environmental protection, the concept of halogen-free flame-retardant cables has gradually emerged. However, halogen-free cables still face great challenges in achieving good flame retardant effects. Since halogen flame retardants cannot be relied upon, it is necessary to find other effective flame retardant mechanisms, such as adding a large amount of halogen-free flame retardants such as metal hydroxides. However, adding too much flame retardants such as magnesium hydroxide may reduce the mechanical properties of the cable material. Therefore, preparing a halogen-free flame retardant cable with good mechanical properties is a problem that needs to be solved at present. Summary of the invention
[0003] The present invention provides a halogen-free flame-retardant environmentally friendly cable, which solves the problem of poor mechanical properties of the halogen-free flame-retardant environmentally friendly cable in the related art.
[0004] The technical solution of the present invention is as follows:
[0005] The present invention provides a halogen-free flame-retardant environmentally friendly cable, which comprises a core, an inner lining layer, an armor layer and a sheath layer from the inside to the outside. The sheath layer comprises the following raw materials in parts by weight: 60-70 parts of polyolefin, 35-45 parts of ethylene-vinyl acetate copolymer, 30-40 parts of flame-retardant filler, 0.8-1 part of lubricant, 1.5-2.5 parts of antioxidant and 2-4 parts of plasticizer; the flame-retardant filler comprises a flame retardant and attapulgite; the mass ratio of the flame retardant to the attapulgite is 5-30:1.
[0006] As a further technical solution, the wire core includes a conductor, a mica tape, and an insulating layer.
[0007] As a further technical solution, the conductor is copper wire and the insulating layer is polyethylene.
[0008] As a further technical solution, the inner lining layer is polypropylene, and the armor layer is galvanized steel strip.
[0009] As a further technical solution, the mass ratio of the flame retardant to the attapulgite is 10-20:1.
[0010] As a further technical solution, the attapulgite is 3-methacrylamide phenyl boric acid modified attapulgite.
[0011] As a further technical solution, the preparation method of the modified attapulgite comprises the following steps: dispersing 3-methacrylamide phenylboric acid and attapulgite in methanol for modification, and obtaining the modified attapulgite after drying.
[0012] As a further technical solution, the added amount of the 3-methacrylamide phenylboric acid is 3% to 6% of the mass of the attapulgite.
[0013] As a further technical solution, the modification temperature is 40-50° C., and the modification time is 5-6 hours.
[0014] As a further technical solution, the flame retardant includes an organic flame retardant and an inorganic flame retardant.
[0015] As a further technical solution, the mass ratio of the organic flame retardant to the inorganic flame retardant is 1:3-5.
[0016] As a further technical solution, the organic flame retardant is melamine polyphosphate, and the inorganic flame retardant is magnesium hydroxide.
[0017] As a further technical solution, the magnesium hydroxide is polysilazane-modified magnesium hydroxide.
[0018] As a further technical solution, the preparation method of the modified magnesium hydroxide comprises the following steps: dissolving polysilazane in acetone, adding magnesium hydroxide for modification, and obtaining the modified magnesium hydroxide after drying.
[0019] As a further technical solution, the added amount of the polysilazane is 3% to 5% of the mass of the magnesium hydroxide.
[0020] As a further technical solution, the modification temperature is 30-40°C and the modification time is 2-3h.
[0021] As a further technical solution, the lubricant includes one or more of stearic acid, zinc stearate, and polyethylene wax.
[0022] As a further technical solution, the antioxidant includes one or more of antioxidant 1010 , antioxidant 168 , and antioxidant 264 .
[0023] As a further technical solution, the plasticizer includes one or more of di-sec-octyl phthalate, dicyclohexyl phthalate, and dibutyl phthalate.
[0024] The present invention also provides a method for preparing a halogen-free flame-retardant environmentally friendly cable, comprising the following steps:
[0025] S1. Wrap mica tape around the outside of the copper wire, and extrude polyethylene around the outside of the mica tape to obtain a wire core;
[0026] S2, extruding polypropylene on the outer side of the wire core to obtain an inner lining layer;
[0027] S3, wrapping the galvanized steel strip around the outer side of the inner lining layer to obtain an armor layer;
[0028] S4. After mixing the raw materials of the sheath layer, extrude it on the outside of the armor layer to obtain a halogen-free, flame-retardant and environmentally friendly cable.
[0029] The working principle and beneficial effects of the present invention are:
[0030] In the present invention, by using polyolefin and ethylene-vinyl acetate copolymer as the base material of the sheath layer, the sheath layer can have a certain flexibility and tensile strength, and adding a flame retardant filler composed of a flame retardant and attapulgite can improve the flame retardancy and mechanical properties of the sheath layer, thereby solving the problem of poor mechanical properties of halogen-free flame retardant cables. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In the following examples and comparative examples:
[0033] Polyolefin, model: AW564; ethylene-vinyl acetate copolymer, model: EVA 460; polysilazane, molecular weight: 900~1000; magnesium hydroxide, particle size: 30~50nm; attapulgite, particle size: 200 mesh.
[0034] Example 1
[0035] A method for preparing a halogen-free flame-retardant environmentally friendly cable comprises the following steps:
[0036] S1. Wrap mica tape around the outside of the copper wire, and extrude polyethylene around the outside of the mica tape to obtain a wire core;
[0037] S2, extruding polypropylene on the outer side of the wire core to obtain an inner lining layer;
[0038] S3, wrapping the galvanized steel strip around the outer side of the inner lining layer to obtain an armor layer;
[0039] S4. Mix 60 parts of polyolefin, 35 parts of ethylene-vinyl acetate copolymer, 30 parts of flame retardant filler, 0.8 parts of stearic acid, 1.5 parts of antioxidant 1010 and 2 parts of di-sec-octyl phthalate, and extrude them on the outside of the armor layer to obtain a halogen-free flame retardant environmentally friendly cable.
[0040] The flame retardant filler is obtained by grinding and mixing a flame retardant and attapulgite in a mass ratio of 5:1, and the flame retardant is magnesium hydroxide.
[0041] Example 2
[0042] A method for preparing a halogen-free flame-retardant environmentally friendly cable comprises the following steps:
[0043] S1. Wrap mica tape around the outside of the copper wire, and extrude polyethylene around the outside of the mica tape to obtain a wire core;
[0044] S2, extruding polypropylene on the outer side of the wire core to obtain an inner lining layer;
[0045] S3, wrapping the galvanized steel strip around the outer side of the inner lining layer to obtain an armor layer;
[0046] S4. Mix 70 parts of polyolefin, 45 parts of ethylene-vinyl acetate copolymer, 40 parts of flame retardant filler, 1 part of polyethylene wax, 2.5 parts of antioxidant 264, and 4 parts of dibutyl phthalate, and extrude them on the outside of the armor layer to obtain a halogen-free flame retardant and environmentally friendly cable.
[0047] The flame retardant filler is obtained by grinding and mixing a flame retardant and attapulgite in a mass ratio of 30:1, and the flame retardant is magnesium hydroxide.
[0048] Example 3
[0049] The only difference between this embodiment and embodiment 2 is that the mass ratio of the flame retardant to attapulgite is 10:1.
[0050] Example 4
[0051] The only difference between this embodiment and embodiment 2 is that the mass ratio of the flame retardant to attapulgite is 20:1.
[0052] Example 5
[0053] The difference between this embodiment and embodiment 3 is that the attapulgite is replaced by an equal amount of modified attapulgite;
[0054] The preparation method of modified attapulgite comprises the following steps: dispersing 1.2 g of 3-methacrylamide phenylboric acid and 40 g of attapulgite in 400 mL of methanol, heating to 50° C., stirring for 5 hours, and drying to obtain modified attapulgite.
[0055] Example 6
[0056] The only difference between this embodiment and embodiment 5 is that the added amount of 3-methacrylamide phenylboronic acid is 2.4 g.
[0057] Example 7
[0058] The only difference between this embodiment and embodiment 6 is that the flame retardant consists of melamine polyphosphate and magnesium hydroxide in a mass ratio of 1:3.
[0059] Example 8
[0060] The only difference between this embodiment and embodiment 6 is that the flame retardant consists of melamine polyphosphate and magnesium hydroxide in a mass ratio of 1:5.
[0061] Example 9
[0062] The only difference between this embodiment and embodiment 8 is that magnesium hydroxide is replaced by an equal amount of modified magnesium hydroxide.
[0063] The preparation method of modified magnesium hydroxide comprises the following steps: dissolving 1.5 g of polysilazane in 500 mL of acetone, adding 50 g of magnesium hydroxide, heating to 35° C., stirring for 3 hours, and drying to obtain modified magnesium hydroxide.
[0064] Example 10
[0065] The only difference between this embodiment and embodiment 9 is that the added amount of polysilazane is 2.5 g.
[0066] Comparative Example 1
[0067] The only difference between this comparative example and Example 1 is that attapulgite is replaced by an equal amount of magnesium hydroxide.
[0068] Comparative Example 2
[0069] The only difference between this comparative example and Example 1 is that in step S4, 60 parts of polyolefin, 35 parts of ethylene-vinyl acetate copolymer, 25 parts of magnesium hydroxide, 5 parts of attapulgite, 0.8 parts of stearic acid, 1.5 parts of antioxidant 1010 and 2 parts of di-sec-octyl phthalate are mixed and extruded on the outside of the armor layer to obtain a halogen-free flame-retardant and environmentally friendly cable.
[0070] Experiment 1
[0071] The halogen-free flame-retardant and environmentally friendly cables prepared in Examples 1 to 10 and Comparative Examples 1 to 2 were respectively tested for the tensile strength of the sheath layer according to the test method in GB / T 2951.11-2018 "General test methods for insulation and sheath materials of cables and optical cables Part 11: General test method for thickness and dimensional measurement mechanical properties test". The specific test method is: the sheath is cut along the cable axis, a narrow strip is cut, a dumbbell specimen is prepared, all cable components in the narrow strip are removed, and the dumbbell specimen is tested for its unaged tensile strength at 23±5°C; the halogen-free flame-retardant and environmentally friendly cables prepared in Examples 1 to 10 and Comparative Examples 1 to 2 were tested for flame retardancy according to the test method in GB / T 18380.33-2022 "Combustion test of cables and optical cables under flame conditions Part 33: Vertical flame spread test type A for vertically installed bundled wires and cables", wherein the number of blowtorches is 1 and the fire supply time is 40 min; the test results are shown in Table 1.
[0072] Table 1 Sheath layer performance test results
[0073]
[0074] Compared with Example 1, no attapulgite was added in Comparative Example 1, and magnesium hydroxide and attapulgite were not mixed in Comparative Example 2. As a result, the tensile strength of the sheath layer prepared in Comparative Examples 1-2 was lower than that in Example 1, and the maximum carbonization range above the bottom edge of the prepared cable blowtorch was greater than that in Example 1, indicating that the addition of a flame retardant filler composed of attapulgite and magnesium hydroxide can improve the mechanical strength and flame retardancy of the cable.
[0075] Compared with Example 3, in Examples 5-6, the attapulgite was modified by 3-methacrylamidephenylboric acid. As a result, the tensile strength of the sheath layer obtained in Examples 5-6 was higher than that in Example 3, indicating that when the attapulgite was modified by 3-methacrylamidephenylboric acid, the mechanical properties of the cable can be further improved.
[0076] Compared with Example 6, the composition of the flame retardant was changed in Examples 7-8. As a result, the tensile strength of the sheath layer obtained in Examples 7-8 was higher than that in Example 6, and the maximum carbonization range above the bottom edge of the cable blowtorch was smaller than that in Example 6, indicating that when the flame retardant is composed of melamine polyphosphate and magnesium hydroxide, the mechanical properties and flame retardancy of the cable can be further improved.
[0077] Compared with Example 8, polysilazane was used to modify magnesium hydroxide in Examples 9-10. As a result, the tensile strength of the sheath layer obtained in Examples 9-10 was higher than that in Example 8, and the maximum carbonization range above the bottom edge of the obtained cable blowtorch was smaller than that in Example 8, indicating that when polysilazane was used to modify magnesium hydroxide, the mechanical properties and flame retardancy of the cable can be further improved.
[0078] Experiment 2
[0079] The low temperature performance of the sheath layer of the halogen-free flame-retardant environmentally friendly cable prepared in Example 1 was tested according to the test method in GB / T 2951.14-2008 "General test methods for insulation and sheath materials of electric and optical cables Part 14: General test methods low temperature test", and the test results are shown in Table 2.
[0080] Table 2 Test results of low temperature performance of sheath layer
[0081]
[0082] It can be concluded from Table 2 that the sheath layer prepared in the present invention has high elongation and impact resistance at low temperatures, indicating that the halogen-free flame-retardant and environmentally friendly cable prepared in the present invention has good low temperature resistance.
[0083] Experiment 3
[0084] The halogen-free flame-retardant and environmentally friendly cable prepared in Example 1 was tested for bromine and chlorine contents according to the test method in GB / T 17650.1-2021 "Test method for gases released during combustion of materials obtained from cables or optical cables Part 1: Determination of the total amount of halogen acid gases", and the fluorine content in the cable was determined according to the test method in GB / T 7113.2-2014 "Insulating hoses Part 2: Test methods", and the pH value and conductivity of the cable were determined according to the test method in GB / T 17650.2-2021 "Test method for gases released during combustion of materials obtained from cables or optical cables Part 2: Determination of acidity (measured by pH) and conductivity"; the test results are shown in Table 3.
[0085] Table 3 Cable halogen-free performance test results
[0086]
[0087] It can be concluded from Table 3 that the bromine and chlorine contents in the halogen-free flame-retardant and environmentally friendly cable prepared in the present invention are both lower than 0.5%, the fluorine content is lower than 0.1%, the pH value is greater than 4.3, and the conductivity is less than 10 μS / mm, which meets the halogen-free requirements.
[0088] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A halogen-free flame-retardant environmentally friendly cable, characterized in that: From the inside to the outside, it includes a core, an inner lining layer, an armor layer, and a sheath layer. The sheath layer includes the following raw materials in parts by weight: 60-70 parts of polyolefin, 35-45 parts of ethylene-vinyl acetate copolymer, 30-40 parts of flame retardant filler, 0.8-1 part of lubricant, 1.5-2.5 parts of antioxidant, and 2-4 parts of plasticizer; the flame retardant filler includes a flame retardant and attapulgite; the mass ratio of the flame retardant to the attapulgite is 5-30:1; the flame retardant is magnesium hydroxide; the attapulgite is 3-methacrylamide phenyl boric acid modified attapulgite.
2. A halogen-free flame-retardant environmentally friendly cable, characterized in that: From the inside to the outside, it includes a core, an inner lining layer, an armor layer, and a sheath layer. The sheath layer includes the following raw materials in parts by weight: 60-70 parts of polyolefin, 35-45 parts of ethylene-vinyl acetate copolymer, 30-40 parts of flame retardant filler, 0.8-1 part of lubricant, 1.5-2.5 parts of antioxidant, and 2-4 parts of plasticizer; the flame retardant filler includes flame retardant and attapulgite; the mass ratio of the flame retardant to the attapulgite is 5-30:1; the flame retardant is magnesium hydroxide and polyphosphate melamine; the attapulgite is 3-methacrylamide phenyl boric acid modified attapulgite.
3. The halogen-free flame-retardant environmentally friendly cable according to claim 1, characterized in that: The mass ratio of the flame retardant to the attapulgite is 10-20:
1.
4. The halogen-free flame-retardant environmentally friendly cable according to claim 2, characterized in that: The mass ratio of the melamine polyphosphate to the magnesium hydroxide is 1:3-5.
5. The halogen-free flame-retardant environmentally friendly cable according to claim 2, characterized in that: The magnesium hydroxide is polysilazane-modified magnesium hydroxide.
6. A halogen-free flame-retardant environmentally friendly cable according to claim 1 or claim 2, characterized in that: The lubricant includes one or more of stearic acid, zinc stearate, and polyethylene wax.
7. A halogen-free flame-retardant environmentally friendly cable according to claim 1 or claim 2, characterized in that: The antioxidant includes one or more of antioxidant 1010 , antioxidant 168 , and antioxidant 264 .
8. A halogen-free flame-retardant environmentally friendly cable according to claim 1 or claim 2, characterized in that: The plasticizer includes one or more of di-sec-octyl phthalate, dicyclohexyl phthalate, and dibutyl phthalate.
Citation Information
Patent Citations
Attapulgite-synergetic hydroxide flame retardant
CN105968414A